Risk of Diarrhea in Infants on Breastfeeding Exclusive and Non-Exclusive Breastfeeding - Irwan Irwan; Deliyana I. Katili; Mar'atuljannah Una; Mutiara Patricia Ladimo; Desiana Pratiwi Hantulu (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Diarrheal disease is a significant risk factor for morbidity and mortality worldwide in children under five years of age. The study aimed to analyze the risk factors for diarrhea in infants with and without exclusive breastfeeding. The research approach used a case-control analysis with observational analytic methods. The population was all mothers who gave birth to babies aged 6-12 months. By determining the sample using the Lemeshow formula, the example was 152 babies with details of 76 cases and 76 controls. The results of the chi-square test showed (p-value= 0,000), which means that there was an effect of exclusive breastfeeding and non-exclusive breastfeeding with the incidence of diarrhea in infants with a value of OR=12,065, which means that mothers who did not breastfeed their babies 12,065 times more at risk of suffering from diarrhea higher inversely compared to mothers who exclusively breastfeed their babies. In conclusion, infants who are not exclusively breastfed are at risk of suffering from diarrhea than infants who are exclusively breastfed.